Celebrity Instragram tracing the personal narrative of Filipino celebrities on Instagram - Sawit, Andrea Grace B. 1993-; Vinculado, Jane O.; University of the Philippines. College of Mass Communication (2014)
"This study is a textual analysis of the Instagram photographs of three filipino television celebrities; namely Anee Curtis, Vice Ganda, and Nikki Gil. This study aims to trace each celebrity's personal narrative by reading and analyzing their photos, as well as the messages attached to it such as the text of the author and the comments of the readers. By accessing the Internet and viewing the celebrity's Instagram content, this study aims to determine how their personal narrative are manifested. Instagram is a social networking site that allows its users to present and share their lives in creative ways. Through the art of photography and digital editing, users are offered countless options to display their life whether the stories are special events or simply everyday activities. This study establishes the different narrative components that build the structure of personal narrative. An important facet to this is the interplay between the author and reader of the media text. Through this, the multiplicity of narrative participants emerge and are questioned according to grounded concepts of earlier narrative studies. The study is an important tool in understanding online media because narrative plays a constant role in emerging media forms. To quote Roland Barthes, "narrative is present in every age, in every place, in every society; it begins with the very history of mankind and there nowhere is nor has been a people without narrative."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Celebrities -- Philippines; Internet personalities -- Philippines; Online identities -- Philippines; Online social networks -- Philippines